PERAN KOMITE MADRASAH DALAM PEMBIAYAAN PENDIDIKAN DI MADRASAH IBTIDAIYAH NEGERI 1 MAGELANG PERIODE TAHUN 2018-2021 - Abdul Aziz; Khamim Zarkasih Putro; Ary Sutrischastini (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The purpose of this study was to find out why the role of the Madrasah Committee in financing education at MIN 1 Magelang was still not optimal and to analyze efforts to increase the. In qualitative research, data analysis includes three main steps, namely: (1) data reduction, (2) data presentation, (3) drawing conclusions or levers. As a result, the role of the school committee in financing has implemented several related development performance indicators as a consideration body (advisory agency), supporting, controlling and relationship (mediator) institutions in the form of cooperation in the procurement of funds and in school procurement. However, the role of the school committee in financing is still not optimal because the integrity of the management and school committee members at MIN 1 Magelang is still not optimal, schools cannot collect fees, MIN 1 Magelang is a public school so it is difficult to fund other than the three sources BOS Reg, BOSDA, District BOSS. Efforts to increase the role of school committees in financing at MIN 1 Magelang are trying to help find sources of funds for the School Budget and Expenditure Draft (RAPBS) and also students who cannot afford.